Analisis Penggunaan Media Sosial Twitter Sebagai Media Curhat oleh Kalangan Muslim Generasi Z - Zulita Mega Aggriany; Winda Kustiawan (LPPM Institut Nasional Laa Roiba Bogor, 2023)
In general, we know social media as a medium for socializing via the internet without space and time limits so that we can be trusted to have the right to express what we want to share on social media. This then has a connection with one form of interpersonal communication, in the form of self-disclosure (self-disclosure) about our personal information to others and vice versa. Especially in the Z generation group which is famous for its technological prowess. So that researchers are interested in conducting research on whether there is a relationship and the intensity of the use of social media Twitter on the use of media in sharing self-information / venting, especially among Muslim generation Z which is based on forms of interpersonal communication; self-disclosure. The theory used in this paper is the theory of self-disclosure as an activity of self-disclosure. This research is a quantitative research with research methods, survey methods. With a population of Twitter users aged 23-13 years or age category belonging to generation Z. A total of 141 respondents were obtained through a purposive sampling technique. Questionnaires were distributed online via g-form. In processing and analyzing data using IBM SPSS statistics 29 software. In addition, to test the hypothesis, a simple linear regression analysis is used. The results showed that it was concluded that the variable use of Twitter social media has a relationship with the variable use of confinement media if it is based on the t value. count as 9,188. From the results of these calculations then t. calculate 9.188 > t. table 1.977. It can be concluded that the variable use of social media Twitter has an influential relationship with the use of social media by generation Z Muslims. Keywords: Social Media, Twitter, Self Disclosure, Confide, Generation Z